The landscape of miRNA editing in animals and its impact on miRNA biogenesis and targeting - Li, Lishi (Genome Res, 2018)
Adenosine-to-inosine (A-to-I) RNA editing regulates miRNA biogenesis and function. To date, fewer than 160 miRNA editing sites have been identified. Here, we present a quantitative atlas of miRNA A-to-I editing through the profiling of 201 pri-miRNA samples and 4694 mature miRNA samples in human, mouse, and Drosophila. We identified 4162 sites present in ∼80% of the pri-miRNAs and 574 sites in mature miRNAs. miRNA editing is prevalent in many tissue types in human. However, high-level editing is mostly found in neuronal tissues in mouse and Drosophila. Interestingly, the edited miRNAs in neuronal and non-neuronal tissues in human gain two distinct sets of new targets, which are significantly associated with cognitive and organ developmental functions, respectively. Furthermore, we reveal that miRNA editing profoundly affects asymmetric strand selection. Altogether, these data provide insight into the impact of RNA editing on miRNA biology and suggest that miRNA editing has recently gained non-neuronal functions in human.